1987
DOI: 10.1088/0022-3727/20/8/015
|View full text |Cite
|
Sign up to set email alerts
|

Railgun recoil and relativity

Abstract: A recent communication by Graneau (see ibid., vol.20, p.391, 1987) on railgun recoil and relativity is refuted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The problem is known from experimental and theoretical studies 3,42,55 and arises due to differences in the shape of the diffusion layer boundary. 47 Over large mask openings or dense patterns of small mask openings the diffusion layer boundary is parallel to the surface and mass transfer occurs in one dimension only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem is known from experimental and theoretical studies 3,42,55 and arises due to differences in the shape of the diffusion layer boundary. 47 Over large mask openings or dense patterns of small mask openings the diffusion layer boundary is parallel to the surface and mass transfer occurs in one dimension only.…”
Section: Resultsmentioning
confidence: 99%
“…Concentration gradients along the edge of a pattern of mask openings can be leveled by introducing so-called current robber areas surrounding the pattern. 3 Also, large mask openings can be divided into a number of smaller mask openings, a large chamber thus being formed by the merging of many smaller cavities. 42,55 In theory reducing the thickness of the diffusion layer via forced convection should also reduce the dependence of the etch rate on size effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention has been focused on the force on an end conductor connecting two parallel rails which is either stationary or moving, in the latter case as the projectile of an electromagnetic railgun (Graneau 1987). The railgun recoil is caused partly by the mechanical momentum imparted to the projectile and partly by the electromagnetic momentum created in the field, although the latter is very small for non-relativistic velocities (Allen 1987).…”
mentioning
confidence: 99%
“…The corrections looked for in experiments of this type are usually very small. Indeed, for forces in the direction of the motion as in the railgun (Graneau 1987, Allen 1987, it can be shown that, if the moving frame electric field may be neglected, there are no differences even in the highly relativistic case. For the present example, however, the difference in the highly relativistic case would be large.…”
mentioning
confidence: 99%